If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 27 = 9p Reorder the terms: 27 + 6p = 9p Solving 27 + 6p = 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. 27 + 6p + -9p = 9p + -9p Combine like terms: 6p + -9p = -3p 27 + -3p = 9p + -9p Combine like terms: 9p + -9p = 0 27 + -3p = 0 Add '-27' to each side of the equation. 27 + -27 + -3p = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -3p = 0 + -27 -3p = 0 + -27 Combine like terms: 0 + -27 = -27 -3p = -27 Divide each side by '-3'. p = 9 Simplifying p = 9
| ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 | | 8-(4n-8)=-8 | | 2(x-1)=3x-7 | | 25-2x=15 | | 1.8x-8=22 | | 2x-(-4)=96+(-10) | | 3x+4y=9.4 | | 4z/6-6=5 | | d/12-6=1 | | -8x+2=74 | | 6=-3+v | | -18a/6 | | 3x+4x=9.4 | | f(x)=3x^4-13x^2+14 | | 1.8q-5.4-1.7q=-0.9q-5.1 | | 2(5c-5.1)=-20.1 | | 128=-t^2+6t | | 22+7=3(22)-3 | | 2(x+3)=x+5+x | | 2(3x+1)=10x-6 | | Rx+sy=16 | | 4+14p-1=8p+87-6p | | 9x+18=6x+21 | | 2p+1=p+3 | | t^2-6t+128=0 | | 2(2)-3=0 | | 6x^2-24x-72=32 | | (4x)(2)=(3x)(243) |